2020
DOI: 10.1097/ico.0000000000002352
|View full text |Cite
|
Sign up to set email alerts
|

Descemet Membrane Detachment After Penetrating Keratoplasty for Keratoconus

Abstract: Purpose: To describe risk factors, management and outcome of delayed Descemet membrane (DM) detachment following penetrating keratoplasty (PK) for keratoconus.Methods: We report seven eyes and combine this data with seven previous case reports identified by a search of PubMed.Results: DM detachment occurred at a median of 25 years (range, 7 to 33 years) following PK. One individual had bilateral detachments. There was typically mild ocular discomfort accompanied in some cases by a rapid onset of visual blur. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…8,9 However, in recent AS-OCT examinations, a DM break was identified only in a subset of patients (4 of 14 eyes). 4 Several modalities for the treatment of late DMD have been proposed. 2–7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 However, in recent AS-OCT examinations, a DM break was identified only in a subset of patients (4 of 14 eyes). 4 Several modalities for the treatment of late DMD have been proposed. 2–7…”
mentioning
confidence: 99%
“…A special situation is DMD occurring late after penetrating keratoplasty (PK): Several case reports and series have described patients with a history of PK who developed a sudden or insidious visual deterioration due to DM detachment. [2][3][4][5][6][7][8][9][10][11] Kit et al 4 described DMD in 14 cases, in which PK had been performed at a median of 25 years ago, and found that DMD was often misdiagnosed as late graft rejection because the presentation with (sub)acute onset of corneal edema can be similar.…”
mentioning
confidence: 99%
“…Delayed-onset DMD has been reported following PKP for corneal ectasias such as keratoconus and pellucid marginal degeneration. [ 6 7 ] Other reports described it as acute hydrops with detectable breaks in DM using anterior segment OCT.[ 8 ] The mechanism of DMD following PKP for keratoconus is unclear. Some authors proposed the presence of a retro-corneal membrane along the graft–host interface that can cause mechanical detachment of DM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] However, some cases require further intervention such as endothelial keratoplasty or regraft. [ 5 6 ] Our patient was treated successfully with air injection and the cornea was clear within 10 days following the procedure. However, the vision improved minimally due to advanced glaucomatous optic nerve damage and amblyopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation